2019
DOI: 10.17811/ebl.8.1.2019.17-30
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences, risk attitude and entrepreneurship in Kyrgyzstan

Abstract: This study analyses the role of risk attitude for entrepreneurship by gender differences in Kyrgyzstan. Logit analysis is applied to the cross-sectional data set drawn from the nationally representative survey for 2011. Entrepreneurship is measured by the self-employment activities and analysed by the agricultural and non-agricultural sample. Results of the study show that more risk-taking preferences are associated with higher entrepreneurship probability. However, this effect is not persistent for women in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…En investigaciones en zonas rurales como en Wang y Zhou (2022) encuentran que el uso del internet (48,0 %) incrementa la probabilidad en jóvenes chinos. En Kirguistán, Abdieva et al (2019) los emprendimientos agrícolas son menos probables en hombres debido a una mayor preferencia al riesgo (-12,1 %).…”
Section: Antecedentesunclassified
“…En investigaciones en zonas rurales como en Wang y Zhou (2022) encuentran que el uso del internet (48,0 %) incrementa la probabilidad en jóvenes chinos. En Kirguistán, Abdieva et al (2019) los emprendimientos agrícolas son menos probables en hombres debido a una mayor preferencia al riesgo (-12,1 %).…”
Section: Antecedentesunclassified
“…Międzynarodowe badania naukowe sugerują, iż prowadzenie własnej działalności gospodarczej w przypadku kobiet i mężczyzn różni się pod wieloma względami [Veena, Nagaraja 2013]. Przykładowo różnice te dotyczą: motywacji do prowadzenia własnego biznesu [VISA 2019], skłonności do podejmowania ryzyka [Abdieva, Sulaimanova, Karymshakov 2019], tworzenia sieci i udziału w sieciach społecznych [Klyver, Grant 2010], celów do realizacji w biznesie [Gottschalk, Niefert 2013], finansowania działalności gospodarczej [McGrath Cohoon, Wadhwa, Mitchell 2010], zasobów kapitału ludzkiego [Khalife, Chalouhi 2013], stylu kierowania firmą [Burke, Collins 2001], sposobu zarządzania biznesem [Mukhtar 2002] oraz wyników ekonomicznych [Fairlie, Robb 2008].…”
Section: Dariusz Leszczyńskiunclassified
“…Much evidence has demonstrated that there is a significant positive correlation between entrepreneurship and economic growth (Navarro, et al, 2009;Abdieva et al 2019;Chienwattanasook & Jermsittiparsert, 2019;Otache 2019a;Lopes et al, 2020;Velilla & Ortega, 2020;Mukwarami et al, 2020). Entrepreneurship is regarded as one of the key elements to economic success, making a significant contribution to resolving unemployment problems, critically important at a time when a number of countries, both developed and emerging, are facing difficulties with graduate unemployment (Ahmad & Xavier, 2012;Ndofirepi, 2016;Farrukh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%